1995
DOI: 10.1523/jneurosci.15-03-01768.1995
|View full text |Cite
|
Sign up to set email alerts
|

Stress and glucocorticoids affect the expression of brain-derived neurotrophic factor and neurotrophin-3 mRNAs in the hippocampus

Abstract: Chronic stress produces structural changes and neuronal damage especially in the hippocampus. Because neurotrophic factors affect neuron survival, we questioned whether they might be relevant to the heightened vulnerability of hippocampal neurons following stress. To begin investigating this possibility, we examined the effects of immobilization stress (2 hr/d) on the expression of neurotrophic factors in rat brains using in situ hybridization. We found that single or repeated immobilization markedly reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
732
15
20

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,315 publications
(828 citation statements)
references
References 46 publications
51
732
15
20
Order By: Relevance
“…20 However, there were no differences in baseline BDNF mRNA levels comparing two other strains of rats, one bred for helplessness in response to stress (cLH) and the other based on selection for resistance (cNLH). 99 These results are not consistent with the findings of other researchers using models of stress-induced depression, 17,21,22 where decreased central BDNF was demonstrated. Unchanged or increased BDNF levels in animal models of depression compared to controls would seem to be at variance with the assumed decreased CNS BDNF in human depression.…”
Section: Bdnf and Animal Models Of Depressioncontrasting
confidence: 74%
See 2 more Smart Citations
“…20 However, there were no differences in baseline BDNF mRNA levels comparing two other strains of rats, one bred for helplessness in response to stress (cLH) and the other based on selection for resistance (cNLH). 99 These results are not consistent with the findings of other researchers using models of stress-induced depression, 17,21,22 where decreased central BDNF was demonstrated. Unchanged or increased BDNF levels in animal models of depression compared to controls would seem to be at variance with the assumed decreased CNS BDNF in human depression.…”
Section: Bdnf and Animal Models Of Depressioncontrasting
confidence: 74%
“…A genetic link between neurotrophins and schizophrenia is supported by the evidence that polymorphisms of the NT-3 and BDNF genes are associated with schizophrenia. [7][8][9] Lastly, findings that BDNF is decreased by factors correlated with first episode onset, such as stress 59,21 and estrogen withdrawal, 60 are also consistent with the putative BDNF role in schizophrenia. Interestingly, these stress-induced decreases in BDNF are blocked by 5-HT2 receptor antagonists, a receptor binding property of many neuroleptics.…”
Section: Animal Modelsmentioning
confidence: 55%
See 1 more Smart Citation
“…Further implicating a role for BDNF signaling in depression and anxiety, it has been shown that decreases in hippocampal BDNF levels are correlated with stressinduced depressive behaviors (Nibuya et al, 1995;Smith et al, 1995;Vaidya et al, 1997;Duman, 2004;Duman and Monteggia, 2006), and that antidepressant treatment enhances the expression of BDNF (Nibuya et al, 1995;Russo-Neustadt et al, 1999;Duman and Monteggia, 2006). Moreover, the BDNF gene as well as the Val66Met polymorphism have been associated with increased risk for a number of neuropsychiatric disorders (Neves-Pereira et al, 2002;Sklar et al, 2002;Schumacher et al, 2005;Strauss et al, 2005;Okada et al, 2006).…”
Section: Bdnfmentioning
confidence: 99%
“…This factor has been found diminished in the rat hippocampus after acute and chronic stress (Smith et al, 1995;Scaccianoce et al, 2003) and has proved to possess antidepressant action in different models of depression (Shirayama et al, 2002). Moreover, chronic treatment with FLX promotes BDNF expression in the rat hippocampus (De Foubert et al, 2004) that in turn leads to activation of genes and biochemical pathways involved in plasticity and survival (Mattson et al, 2004).…”
Section: Flx-induced Synaptic Remodeling and Behavioral Responsementioning
confidence: 99%